2012
DOI: 10.2139/ssrn.2079598
|View full text |Cite
|
Sign up to set email alerts
|

The Visitors’ Perception of Authenticity at the Museums: Archaeology Versus Modern Art

Abstract: The aim of this paper is to analyse quantitatively the visitors' perception of authenticity in two different types of museums: archaeology versus modern and contemporary art.The research is based on 1,288 questionnaires collected from June to September 2011 among the visitors of the South Tyrol Museum of Archaeology (ÖTZI) in Bolzano and the Museum of Modern and Contemporary Art (MART) in Trento-Rovereto. Logit models were used in order to estimate the set of independent variables that significantly influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…Working on the quality of the temporary exhibition could also be useful in this respect. Interesting indications were noted by Brida et al (2012b), who found that temporary exhibition spaces were significantly perceived as authentic only for MART visitors, and not for ÖTZI. That paper stressed that 'the type of exhibition hosted by the museum can be of great importance for curators and managers in order to increase the perception of authenticity of the attraction' (Brida et al, 2012b, p 8).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Working on the quality of the temporary exhibition could also be useful in this respect. Interesting indications were noted by Brida et al (2012b), who found that temporary exhibition spaces were significantly perceived as authentic only for MART visitors, and not for ÖTZI. That paper stressed that 'the type of exhibition hosted by the museum can be of great importance for curators and managers in order to increase the perception of authenticity of the attraction' (Brida et al, 2012b, p 8).…”
Section: Resultsmentioning
confidence: 96%
“…This separates the spending decision into the stages of 'whether' and 'how much' to spend. This model has been used widely in different fields, such as the evaluation of public goods (Saz-Salazar and Rausell-Köster, 2008;López-Mosquera and Sánchez, 2011;Marzetti et al, 2011;Marzetti and Disegna, 2012), food expenditure (Newman and Matthews, 2001;Bai et al, 2010), analysis of consumption (Jones and Yen, 2000;Aristei and Pierani, 2008), and visitors' expenditure (Hong et al 1999;Weagley and Huh, 2004;Hong et al, 2005;Nicolau and Màs, 2005;Jang et al, 2007;Jang and Ham, 2009;Kim et al, 2010;Brida et al, 2012b). Cragg's (1971) approach estimates a probit model for the first stage, whereas a log-normal or truncated normal model is used for the amount of spending.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nonetheless, 'cultural' tourism is not a facsimile of 'serious' tourism, and can include more casual travel (Brida et al, 2014). Extant literature identifies distinct types of cultural tourist: those curious about the culture surrounding a destination, and those who simply have an interest in experiencing something different while travelling (Richards, 2002).…”
Section: Host Sincerity and Related Conceptsmentioning
confidence: 99%
“…Second, as Gilmore and Pine (2007) point out, individuals consider collections in a museum as naturally authentic because they have been validated by experts (meeting the definition of objective authenticity). Individuals may instead evaluate the authenticity of museums as edifices (Brida, Disegni, and Scuderi 2014; Gilmore and Pine 2007), and, in this case, their evaluation of authenticity relies more on their perception of the building, relating to the constructed authenticity definition we test in this study.…”
Section: Studymentioning
confidence: 99%